2008
DOI: 10.1029/2006tc002060
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology of the southernmost Longitudinal Valley fault: Implications for evolution of the active suture of eastern Taiwan

Abstract: In order to understand fully the deformational patterns of the Longitudinal Valley fault system, a major structure along the eastern suture of Taiwan, we mapped geomorphic features near the southern end of the Longitudinal Valley, where many well‐developed fluvial landforms record deformation along multiple strands of the fault. Our analysis shows that the Longitudinal Valley fault there comprises two major strands. The Luyeh strand, on the west, has predominantly reverse motion. The Peinan strand, on the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 24 publications
13
56
0
Order By: Relevance
“…Most of the long-term slip rates were determined by vertical offset observed either in borehole data (e.g., Chen et al 2008a) or by the deformation of surfaces (e.g., Shyu et al 2008). However, the horizontal offsets by strike-slip structures are difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the long-term slip rates were determined by vertical offset observed either in borehole data (e.g., Chen et al 2008a) or by the deformation of surfaces (e.g., Shyu et al 2008). However, the horizontal offsets by strike-slip structures are difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
“…The seismicity of this fault also illuminated that it has a listric shape, dipping at 75° to a depth of 5.0 km, 60° between 5.0 -15.0 km deep, and finally 45° to a depth of 20.0 km. Several previous studies reported that the slip rate of this fault is between 20.5 -32 mm yr -1 (Chen 2006(Chen , 2010Shyu et al 2006bShyu et al , 2008. However, this fault is also known for its aseismic creeping (e.g., Angelier et al 1997;Lee et al 2001).…”
Section: Seismogenic Structures Of Taiwan and Their Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)). During the past decades, scientists have carried out a variety of quantitative and qualitative analyses to better understand the processes of the plate suture zone in this arc-continent collision (Hsu, 1962;Barrier et al, 1982;Ho, 1986;Yu and Liu, 1989;Yu et al, 1992;Lee and Angelier, 1993;Angelier et al, 1997;Lee et al, 1998;Hu et al, 2001;Yu and Kuo, 2001;Shyu et al, 2008). Efforts from previous studies indicated a rapid shortening of about 30 mm/year in the middle and southern segments of the Longitudinal Valley Fault (LVF), which is the major fault of the plate suture in the valley (Yu et al, 1992;Yu and Kuo, 2001;Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the study area of the southernmost Longitudinal Valley, along the Luyeh River there exist several (5 -7) levels of Holocene river terraces (Shyu et al 2002). The uppermost two terraces are the laterite gravels layers, which are widely distributed in the highlands of the Peinan tableland and the Kaotai tableland with a 14 C age of about 3500 yr (Shyu et al 2008). The heights of these Holocene young terraces are up to 70 m with respect to the present Luyeh riverbed, indicating a rigorous tectonic and erosion activity (i.e., a combining rate of 2 cm yr -1 for terrace uplift and river incision) in the study area.…”
Section: Introductionmentioning
confidence: 99%